(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Oral health is an essential component of health throughout life. However millions of individuals suffer from dental caries and periodontal disease, resulting in unnecessary pain, difficulty in chewing, swallowing and speaking and increased medical costs. To access the prevalence of dental caries among 6- 12 year old children, using available data from hospital case records. The study was conducted to evaluate the oral health status and treatment needs which could be used to plan community based oral health promotion, fluorides and preventive oriented public dental health care services. The study was conducted among 1276 childrens who visited Private Dental hospitals of age groups between 6 to 18 years. Data was collected and tabulated in Excel. Data was analysed using SPSS. Even though dental caries increase with age, no significant difference was found between the age group with respect to oral health status and treatment needs. In the present study, it has been concluded that Dental health education and caries preventive programs are needed to minimize caries among children.